Human Dignity and Human Rights: Fostering and Protecting Pluralism and Particularity - Kirchschläger, Peter G. (Interdisciplinary journal for religion and transformation in contemporary society, 2020)
Human rights and their universality can lead to restrictions for individuals resulting from duties, which correspond to human rights of all human beings. This characteristic of human rights emphasizes the need for an ethical justification. Addressing the question of how human rights can be justified represents, therefore, an expression of respect for pluralism and particularity. Beyond that, human dignity and human rights lay the foundation for pluralism and particularity as they see all human beings as individuals that are all different and unique, and not as members of a collective. Only human rights protection of the autonomy of each individual allows all human beings to be particular and fosters pluralism. Finally, the concept of “adaptation” contributes to an understanding of the interaction between pluralism and particularity and human dignity and human rights as their foundation by capturing the relationship between human dignity and human rights and religious and worldview-based communities.